Versatility of the medial gastrocnemius muscle flap in reconstructing lower limb soft tissue lesions - Jefferson Lessa Soares de Macedo; Simone Corrêa Rosa; Adilson Alves da Silva; Altino Vieira de Rezende Filho Neto; Pedro Henrique Silva Ruguê; Cristiano Scartazzini (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Covering complex lower limb wounds is a major challenge. The medial gastrocnemius muscle flap is usually indicated for reconstruction of loss of substance of the knee and proximal third of the leg. The objective of this study was to evaluate the results using gastrocnemius muscle flaps in lower limb wounds. METHODS: A total of 28 patients with loss of substance in the lower limbs were treated with medial gastrocnemius muscle flaps. Data were obtained from clinical records of patients who underwent surgery from 2003 to 2012. RESULTS: In 28 patients who underwent surgery, the age range was 4 to 57 years, with a mean of 30.6 years. The etiology of the lesions was a motorcycle accident in 16 cases (57.1%), being run over in 8 cases (28.6%), car crash in 2 cases (7.2%), meningococcemia in 1 case (3.6%), and snake bite in 1 case (3.6%). After an average follow-up of 15 months (range: 6 to 26 months), all patients had stable coverage. The mean number of preoperative debridements was 2.4 (range: 1 to 8). In 22 patients, the flaps were made without the release of the muscle origin and in 6 patients the muscle flaps were separated from their origin in the femur. CONCLUSIONS: Transfer of a gastrocnemius muscle flap is a simple and safe procedure in the treatment of lower limb injuries. The application of the medial gastrocnemius muscle flap was demonstrated in different situations, with satisfactory results and easy reproducibility.